Cis-regulatory Evolution of Chalcone-Synthase Expression in the Genus Arabidopsis - de Meaux, Juliette (Copyright © 2006 by the Genetics Society of America, 2006)
The contribution of cis-regulation to adaptive evolutionary change is believed to be essential, yet little is known about the evolutionary rules that govern regulatory sequences. Here, we characterize the short-term evolutionary dynamics of a cis-regulatory region within and among two closely related species, A. lyrata and A. halleri, and compare our findings to A. thaliana. We focused on the cis-regulatory region of chalcone synthase (CHS), a key enzyme involved in the synthesis of plant secondary metabolites. We observed patterns of nucleotide diversity that differ among species but do not depart from neutral expectations. Using intra- and interspecific F(1) progeny, we have evaluated functional cis-regulatory variation in response to light and herbivory, environmental cues, which are known to induce CHS expression. We find that substantial cis-regulatory variation segregates within and among populations as well as between species, some of which results from interspecific genetic introgression. We further demonstrate that, in A. thaliana, CHS cis-regulation in response to herbivory is greater than in A. lyrata or A. halleri. Our work indicates that the evolutionary dynamics of a cis-regulatory region is characterized by pervasive functional variation, achieved mostly by modification of response modules to one but not all environmental cues. Our study did not detect the footprint of selection on this variation.